Comparison Of Progesterone-Induced Blocking Factor Serum Levels In Preterm Labor And Preterm Pregnancy - Patrick Bayu; Johanes C Mose; Muhammad Alamsyah (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Preterm labor is a multifactorial phenomenon involving inflammatory processes that will affect the balance of Th1 to Th2 by increasing dominance of pro-inflammatory Th1 cytokines and also lead to functional progesterone withdrawal.Progesterone maintains pregnancy mainly by promoting myometrial quiescence and labor is initiated by progesterone withdrawal. Progesterone also has antiinflammatory properties and as an immunomodulator. While it has been postulated that the effect of progesterone on preterm birth is related to its anti-inflammatory properties, the spesific mechanism of action remains unclear.The biological effects of progesterone are mediated by a 34-kDa protein named the progesterone-induced blocking factor (PIBF). PIBF is synthesized by lymphocytes of healthy pregnant women in the presence of progesterone. PIBF inhibits arachidonic acid production, reduced NK cell activity, and modifies the cytokine balance.The objective of this study was to compare serum concentrations of PIBF of women with preterm labor with those women with normal pregnancy. A comparative analytical study with cross-sectional design was conducted. This study consisted of 16 women in each group. All the subjects met the inclusion criteria and were admitted to the Dr . Hasan Sadikin hospital and it’s district hospital. This study conducted from July until November 2013. Serum PIBF concentrations were measured by enzyme-linked immunosorbent assay ( ELISA) .Mean PIBF concentrations in serum of patients with preterm labor were significantly lower (391.4051 ± 1021.162 ng/mL ) than in those of normal pregnancy (174.2165 ± 1297.675 ng/mL) with p = 0.029 . It was concluded that the levels of serum PIBF preterm labor is lower than in normal pregnancy.